PLACE, SPACE AND IDENTITY THROUGH GREENING IN KAMPUNG KOTA - Putra, Bagas Dwipantara; Horne, Ralph; Hurley, Joe (Journal of Regional and City Planning, 2019)
As an integral part of the urban landscape in Indonesian cities, kampung kota (urban villages) provide shelter for many marginalised urban dwellers. The presence of green open space in kampung kota has multiple meanings, one of which is the significance it has for the socio-cultural identity of the inhabitants. This article explores the meaning of green open space for kampung dwellers and how it fits in the dynamics of space creation in kampung kota. The methodology employed in this research was a qualitative approach, which was applied in two case studies of separate communities in South Jakarta to understand the meaning of space from their perspective. Based on the findings, green open space plays a significant role in building a community?s identity through shared memories and communally agreed images of the neighbourhood, thus confirming the importance of the community in place-making processes in kampung kota.Abstrak. Sebagai bagian integral dari lanskap perkotaan di kota-kota Indonesia, kampung kota (desa kota) menyediakan tempat berteduh bagi banyak penduduk kota yang terpinggirkan. Kehadiran ruang terbuka hijau di kampung kota memiliki banyak makna, salah satunya adalah signifikansinya bagi identitas sosial-budaya penduduk. Artikel ini mengeksplorasi makna ruang terbuka hijau bagi penghuni kampung dan bagaimana ruang itu sesuai dengan dinamika penciptaan ruang di kampung kota. Metodologi yang digunakan dalam penelitian ini adalah pendekatan kualitatif, yang diterapkan dalam dua studi kasus komunitas terpisah di Jakarta Selatan untuk memahami makna ruang dari perspektif mereka. Berdasarkan temuan tersebut, ruang terbuka hijau memainkan peran penting dalam membangun identitas komunitas melalui ingatan bersama dan gambar yang disepakati bersama tentang lingkungan, sehingga menegaskan pentingnya masyarakat dalam proses pembuatan tempat di kampung kota.Kata kunci. Identitas, kampung kota, komunitas, pembuatan tempat.